The Dynamics of Legal Standardization: A Study of Statutory Codification and Administrative Authority - Rifqi Khairul Anam; Fareed Ahmad Obaidy (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2025)
The dynamics of legal standardization are frequently characterized as a necessary mechanism for achieving administrative certainty and systematic order. This research examines the structural and functional changes that occur during the transition from decentralized interpretive frameworks to centralized statutory systems. Utilizing a structural diagnostic approach, the study evaluates how the integration of traditional norms into a formal administrative framework reconfigures the nature of legal authority. The findings indicate that the standardization process involves the relocation of interpretive validity from decentralized professional networks to centralized institutional bodies, establishing a bureaucratic system governed by modern administrative standards. This transition provides a basis for clarifying institutional roles, where statutory regulations function as distinct administrative instruments. These findings offer a necessary framework for stakeholders, including policy developers, judicial officers, and academic researchers, to navigate the shift toward formalized legal codes. The study concludes by suggesting that the institutionalization of diverse practices necessitates a comprehensive evaluation of the suitability of centralized state mechanisms for managing complex social and professional norms within a standardized regulatory environment.